ON THE USE OF APPARENT HYDRAULIC DIFFUSIVITY AS AN INDICATOR OF CONNECTIVITY - Knudby C.; Carrera J. (My University, 2006)
Connectivity of high permeability paths is recognized as important but has not been properly quantified in the groundwater literature. In fact, it has been shown that the concept is process dependent and difficult to define so that it applies both to water flow and solute transport phenomena. Field and numerical evidence from hydraulic tests suggest that the apparent hydraulic diffusivity, Da, could potentially inform about the phenomena. In order to test this conjecture, we present a Monte Carlo analysis based on series of fields that display varying degrees of connectivity. Our results confirm that Da does indeed indicate the presence of connectivity. Da is found to correlate well with early tracer arrival time, and also with the product of a flow connectivity indicator, CF, and a transport connectivity indicator, CT. This indicates that Da accounts both for connectivity effects controlling the average plume movement (through CF) and for connectivity effects not linked to the effective medium properties that control the progression of the solute front (through CT). Analysis of seven binary fields suggests that flow connectivity hinges more on the continuity of fast paths, whereas transport connectivity seems to be more dependent on the width of connected features forming, possibly discontinuous, fast paths. In conjunction with previous studies, our results suggest that hydraulic response arrival times and early arrival times of tracer can be expected to correlate well in most types of hydrogeologic systems. © 2006 Elsevier B.V. All rights reserved.
Keywords: CONNECTIVITY; CONTAMINANT TRANSPORT; DIFFUSIVITY; HETEROGENEOUS MEDIA; PUMPING TEST; TRACER TEST